Reflecting on Equity in Perinatal Care During a Pandemic (Mary Ann Liebert, 2020)
Growing discourse around maternity care during the pandemic offers an opportunity to reflect on how this crisis has amplified inequities in health care. We argue that policies upholding the rights of birthing people, and policies decreasing the risk of COVID-19 transmission are not mutually exclusive. The explicit lack of standardization of evidence-based maternity care, whether expressed in clinical protocols or institutional policy, has disproportionately impacted marginalized communities. If these factors remain unexamined, then it would seem that equity is not the priority, but retaining power and control is. We advocate for a comprehensive understanding of how this pandemic has revealed our deepest failures.